(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The solvatochromic effect is high in conjugate compounds and easy to observe by the colour change emitted when the solutions are exposed to UV light. It was found in a series of aminofluorene thiophene derivatives, previously synthesized, that irradiating at different wavelengths, the same pattern is obtained, i.e. a dual behaviour in the solvatochromism of the studied compounds. For each one, a bathochromic and hypsochromic effect exists, in polar and nonpolar solvents, respectively. Wavelength vs. polarity index plots clearly showed the abovementioned dual behaviour as well as the improved linearity in its plots. Amidst the wavelengths at which each compound is excited in each solvent, 280 nm was selected as the fixed wavelength for the measurements; (E)-9,9-diethyl-N-hexyl-N-phenyl-7-(2-(thiofen-2-yl)vinyl)-9H-fluoren-2-amine (M6-6) exhibits better linearity as compared to the other studied compounds, being the best to be proposed as polarity sensor or indicator.